2009
DOI: 10.1002/qua.22294
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study on the LaF3 molecule embedded in argon matrix

Abstract: ABSTRACT:The LaF 3 ⅐Ar n (n ϭ 1-21) clusters have been proposed as models to account for the matrix effects on the molecular properties of the LaF 3 molecule isolated in argon solid matrix at cryogenic temperature. Because of the strong Lewis acid character of the LaF 3 molecule, there is a substantial electron-density transfer from the argon atoms to the molecule that induces important geometrical changes in the structure and vibrational frequencies. The present bottom-up approach reveals the formation of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Tsukamoto and co-workers found that dynamic electron correlation is indispensable for obtaining reliable bond distances, whereas static electron correlation has only little influence . For DyX 3 (X = Cl, Br, I), it has been found that 4f subshell does not influence the geometry of the monomers, but obviously affects their dimers (DyX 3 ) 2 (X = Cl, Br, I). ,, According to the calculations, DyX 3 (X = Br, I) probably forms both planar and pyramidal DyX 3 units in an inert matrix, leading to the appearance of two symmetric stretching frequencies observed by the experimentalists. , Similarly, nearby C 3 v and D 3 h structures were found for LaF 3 in Ar n clusters ( n = 1–21) at the MP2 level by Lanza using the shape-consistent La PP of Stevens et al…”
Section: Selected Applicationsmentioning
confidence: 94%
“…Tsukamoto and co-workers found that dynamic electron correlation is indispensable for obtaining reliable bond distances, whereas static electron correlation has only little influence . For DyX 3 (X = Cl, Br, I), it has been found that 4f subshell does not influence the geometry of the monomers, but obviously affects their dimers (DyX 3 ) 2 (X = Cl, Br, I). ,, According to the calculations, DyX 3 (X = Br, I) probably forms both planar and pyramidal DyX 3 units in an inert matrix, leading to the appearance of two symmetric stretching frequencies observed by the experimentalists. , Similarly, nearby C 3 v and D 3 h structures were found for LaF 3 in Ar n clusters ( n = 1–21) at the MP2 level by Lanza using the shape-consistent La PP of Stevens et al…”
Section: Selected Applicationsmentioning
confidence: 94%
“…These species can polarize the electron distribution of the closed-shell noble gases. Examples include molecules involving main group elements and transition metals, 7,8,9,10 lanthanides, 11 and actinides 12, 13 as well. A review on related structures also communicates several cases in which the shape of molecules embedded in matrices is influenced by such interactions.…”
Section: Introductionmentioning
confidence: 99%